2020
DOI: 10.34172/ps.2020.52
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Effects of Probiotic Lactobacillus acidophilus for Colorectal Cancer Cell Line Caco-2 through Apoptosis Induction

Abstract: Background: Colorectal cancer is one of the most common cancers worldwide. Probiotics are useful and non-pathogenic microorganisms in the gastrointestinal tract, which can show anticancer activity through the induction of apoptosis. This study aimed to evaluate the antiproliferative effects of Lactobacillus acidophilus probiotic on the Caco-2 colorectal cancer cell line. Methods: The supernatant (secreted metabolites) and bacterial extract of L. acidophilus probiotics were prepared and used as an anti-prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Lactobacillus acidophilus and Bifidobacterium bifidum showed increased cytotoxic effects against breast and colon cancer cell lines by upregulating Bax, IFN-γ, and TNF-α expression and downregulating Bcl2 expression [41]. Further L. acidophilus induces apoptosis by increasing the mRNA expression of survivin and decreasing the mRNA expression of SMAC [42]. Lactobacillus casei significantly increases the expression of the hBD-2 gene in the cancer colon cell line HT29 [43].…”
Section: Role Of Probiotics In Apoptosis Inductionmentioning
confidence: 99%
“…Lactobacillus acidophilus and Bifidobacterium bifidum showed increased cytotoxic effects against breast and colon cancer cell lines by upregulating Bax, IFN-γ, and TNF-α expression and downregulating Bcl2 expression [41]. Further L. acidophilus induces apoptosis by increasing the mRNA expression of survivin and decreasing the mRNA expression of SMAC [42]. Lactobacillus casei significantly increases the expression of the hBD-2 gene in the cancer colon cell line HT29 [43].…”
Section: Role Of Probiotics In Apoptosis Inductionmentioning
confidence: 99%
“…On the other hand, L. acidophilus and B. bifidum increased the cytotoxic activity against breast and colon cancer cells by upregulating IFN-γ and TNF-α expression, and downregulating Bcl2 expression [260]. Probiotic bacterium L. acidophilus induces apoptosis via increasing the mRNA expression of surviving [261]. Another study revealed that Propionibacterium enhanced apoptosis in colorectal carcinoma cells through the action of SCFAs on mitochondria [262].…”
Section: Probiotics and Cancermentioning
confidence: 99%
“…Probiotic bacterium L . acidophilus induces apoptosis via increasing the mRNA expression of surviving [ 261 ]. Another study revealed that Propionibacterium enhanced apoptosis in colorectal carcinoma cells through the action of SCFAs on mitochondria [ 262 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another treatment for lichen planus is medicinal plants [12][13][14]. Salvia officinalis is one of these plants whose extract is used in salvizan gel.…”
Section: Introductionmentioning
confidence: 99%